Right tracheal sleeve pneumonectomy with VV-ECMO assistance for non-small cell lung cancer through anterior thoracotomy: a single centre experience - Marziali, Valentina; Mangiameli, Giuseppe; Crepaldi, Alessandro; Piccioni, Federico; Costantini, Elena; Citterio, Enrico; Borbone, Alessandro; Cariboni, Umberto (Frontiers in Surgery, 2023)
For a long time, non-small cell lung cancer (NSCLC) arising less than 2 cm distal to the carina has been usually considered unresectable and incurable with a radical or extended resection because of surgical technical difficulty and airway management. Recently, the introduction of more advanced surgical techniques, often including the use of extracorporeal life support (ECLS), has allowed us to extend the limits of conventional surgery, increasing the rate of complete surgical resection. ECLS also overcomes the limitation of conventional ventilation during complex tracheo-bronchial reconstruction, avoiding the presence of disturbing lines or tubes that obstruct the operative field during a challenging surgery. In this article, we share our experience in performing right tracheal sleeve pneumonectomy with veno-venous extracorporeal membrane oxygenation (VV-ECMO) in three cases by anterior right thoracotomy, reporting our tips and tricks.